61. Short- versus prolonged-courses of antimicrobial therapy for patients with uncomplicated Pseudomonas aeruginosa bloodstream infection. (4th December 2021) - Bae, Moonsuk; Jeong, Yun-Seo; Bae, Seongman; Kim, Min Jae; Chong, Yong Pil; Kim, Sung-Han; Lee, Sang-Oh; Choi, Sang-Ho; Kim, Yang Soo; Jung, Jiwon
Abstract: Background: The optimal duration of antimicrobial therapy for uncomplicated Pseudomonas aeruginosa bloodstream infection (BSI) is unknown. We compared the outcomes of short and prolonged courses of antimicrobial therapy in adults with uncomplicated pseudomonal BSI. Methods: All patients with uncomplicated P. aeruginosa BSI admitted at a tertiary-care hospital from May 2016 to September 2020 were included. We compared the rate of recurrent P. aeruginosa infection and 30-day mortality among patients who underwent short (7‒11 days) and prolonged (12‒21 days) courses of antimicrobial therapy using propensity score analysis with the inverse probability of treatment weighting (IPTW) method. Results: We evaluated 1, 477 patients with uncomplicated P. aeruginosa BSI; of them, 290 met the eligibility criteria, including 97 (33%) who underwent short-course therapy (9 [interquartile range (IQR), 8‒11] days) and 193 (67%) who underwent prolonged-course therapy (15 [IQR, 14‒18] days). We found no significant difference in the risk of recurrence or 30-day mortality between the prolonged-course and short-course groups (n=10, 11% vs. n=32, 16%; IPTW-adjusted hazard ratio (HR) 0.61; 95% confidence interval (CI) 0.30−1.24; p =0.17). The recurrence of P. aeruginosa infection at any site within 180 days of completing therapy occurred significantly more in the prolonged-course group (n=10, 10% vs. n=38, 20%; IPTW-adjusted HR 0.48; 95% CI 0.24−0.96, p =0.04). The resistance acquisition in subsequent P. aeruginosa isolates was more frequent in the prolonged-course group, although the difference was not statistically significant (n=2, 20% vs. n=12, 32%; p =0.70). Conclusion: Short-course antimicrobial therapy could be as effective as prolonged-course therapy for uncomplicated P. aeruginosa bloodstream infection. Disclosures: All Authors : No reported disclosures